2008
DOI: 10.1080/08039480801959216
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence, occasional drinking and binge drinking in middle-aged women. The Women's Health in Lund Area (WHILA) Study

Abstract: Although drinking patterns in women have received increased attention, few studies have focused on middle-aged women. Drinking patterns were investigated in a population sample of 513 Swedish women aged 50-59, and analysed in relation to social situation, and mental and physical health. The chi-square test was used to analyse differences in proportions. Variables showing significant differences were entered into a multivariate or multinomial logistic regression model. Abstainers and occasional drinkers had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Binge drinking could be a significant potential health hazard that is not as frequently recognized in middle-aged and elderly adults. In another community survey (6), binge drinking was found to be more common among adults aged ≥26 years than previously estimated and carried some significant risks. Seventy-three percent of all respondents who reported binge drinking drank moderately not heavily (although those who drank heavily were more likely than those who drank moderately to binge drink).…”
mentioning
confidence: 82%
“…Binge drinking could be a significant potential health hazard that is not as frequently recognized in middle-aged and elderly adults. In another community survey (6), binge drinking was found to be more common among adults aged ≥26 years than previously estimated and carried some significant risks. Seventy-three percent of all respondents who reported binge drinking drank moderately not heavily (although those who drank heavily were more likely than those who drank moderately to binge drink).…”
mentioning
confidence: 82%
“…A similar result was found in a Swedish study on middle-aged women where the abstaining group was found to have both lower education and poorer conditions with respect to social situation and health. Drinking to relieve tension was more common in a binge drinking group with severe mental symptoms (38).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, "diagnostic orphans" of alcohol users among middle-aged and elderly adults have significant health risks compared with those who use alcohol without AUD symptoms. Binge drinking is associated with many health problems or consequences, including falls and automobile accidents (15)(16)(17)(18)29). Given that physicians and other health care professionals are often reticent to ask older adults about their use of alcohol, at-risk subthreshold alcohol use may go undetected.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the accuracy of population estimates and enhance study findings' generalizability, the study sample is drawn from the 2005-2007 NSDUH. We compare the pattern of alcohol use by alcohol diagnostic status, including early onset of alcohol use and binge drinking due to their association with alcohol-related problems (15,(14)(15)(16)(17)(18). We also determine whether different diagnostic groups are associated with distinct profiles in key sociodemographic characteristics, major depression, nicotine dependence, and nonmedical prescription drug use to inform the profile of diagnostic orphans compared with threshold groups.…”
Section: Introductionmentioning
confidence: 99%